KARAKTERISTIK RANGKAIAN EKIVALEN DIODA BLEND ORGANIK P3OT : PCBM - Winda Setya (UIN Sunan Gunung Djati Bandung, 2017)
Has conducted research diode characteristics equivalent circuit of the organic blend P3OT: PCBM. In this study, the blend of P3OT:PCBM was sandwiched between a transparent indium tin oxide (ITO) electrode and an Al backside contact. The current-voltage characteristic of the diode was measured under the dark and illumination. In order to determine the electrical parameters of the diode, we employed an equivalent circuit model developed originally for inorganic diode. As a result, the series resistance decreases while the reverse saturation current density increases by decreasing the thickness of P3OT:PCBM layer. This result may be useful for improving the performance of developing organic diode.